Zolpidem: Efficacy and Side Effects for Insomnia - Amber N. Edinoff; Natalie Wu; Yahya T. Ghaffar; Rosemary Prejean; Rachel Gremillion; Mark Cogburn; Azem A. Chami; Adam M. Kaye; Alan D. Kaye (Health Psychology Research)
# Purpose of Review Insomnia is a common type of sleep disorder defined by an ongoing difficulty initiating or maintaining sleep or nonrestorative sleep with subsequent daytime impairment. The sleep disturbances in insomnia usually manifest as difficulty in falling asleep, maintaining the continuity of sleep, or waking up too early in the morning well before the desired time, irrespective of the adequate circumstances to sleep every night. Insomnia can significantly impact daytime functioning resulting in decreased workplace productivity, proneness to errors and accidents, inability to concentrate, frequent daytime naps, and poor quality of life.